2006
DOI: 10.1111/j.1460-9568.2006.04942.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory integration in the basal ganglia

Abstract: Sensorimotor co-ordination in mammals is achieved predominantly via the activity of the basal ganglia. To investigate the underlying multisensory information processing, we recorded the neuronal responses in the caudate nucleus (CN) and substantia nigra (SN) of anaesthetized cats to visual, auditory or somatosensory stimulation alone and also to their combinations, i.e. multisensory stimuli. The main goal of the study was to ascertain whether multisensory information provides more information to the neurons th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 48 publications
(86 reference statements)
10
118
0
Order By: Relevance
“…Moreover, the double anterograde tracing studies have directly shown the presence of PV neurons that received inputs from different cortical regions (Bolam et al, 2000). Judging from the dense and homogeneous interconnectivity among coupled dendrites seen in the mENK-defined matrix of the posterior striatum and from the occurrence of multimodal sensory cells, it is conceivable that the intricate gap junction networks in this region is involved in the local integration of diverse information streams and might provide the anatomical substrate for cross-modal/submodal computations (Nagy et al, 2006). The anterior striatum was not equipped with so much gap junctional coupling, but it will be an intriguing issue how it is in the primate.…”
Section: Implications In the Striatal Circuitrymentioning
confidence: 99%
“…Moreover, the double anterograde tracing studies have directly shown the presence of PV neurons that received inputs from different cortical regions (Bolam et al, 2000). Judging from the dense and homogeneous interconnectivity among coupled dendrites seen in the mENK-defined matrix of the posterior striatum and from the occurrence of multimodal sensory cells, it is conceivable that the intricate gap junction networks in this region is involved in the local integration of diverse information streams and might provide the anatomical substrate for cross-modal/submodal computations (Nagy et al, 2006). The anterior striatum was not equipped with so much gap junctional coupling, but it will be an intriguing issue how it is in the primate.…”
Section: Implications In the Striatal Circuitrymentioning
confidence: 99%
“…7A; Constantinidis et al, 2001), amygdala (Turner et al, 1980), lower bank of the intraparietal sulcus (area LIP; Fig. 7C; Mazzoni et al, 1996;Anderson, 1997), superior colliculus (Wallace et al, 1993), insula, and caudate nucleus (Nagy et al, 2006).…”
Section: Comparison Of Auditory and Visual Mapsmentioning
confidence: 99%
“…This thesis and any success I achieve is a testament to your hard work as loving parents. The basal ganglia (BG) are an important part of a complex neural network that processes and integrates various sensory inputs in order to produce and modulate motor outputs (Contreras-Vidal, 1999;Graziano & Gross, 1993;Houk & Wise, 1995;Nagy, Eordegh, Paroczy, Markus, & Benedek, 2006). Boecker and colleagues termed the BG a "sensory analyzer" engaged in central somatosensory control, suggesting interconnections between the cortex, BG and thalamus that make up an indirect BG-sensory loop (Boecker et al, 1999b).…”
Section: Acknowledgementsmentioning
confidence: 99%